Damped superconducting structure for EUV light source based on energy recovery linac - Taro Konomi; Kensei Umemori; Hiroshi Sakai; Eiji Kako; Tomoko Ota; Atsushi Miyamoto (Physical Review Accelerators and Beams, 2023)
A 10-kW-class high-power extreme ultraviolet light source is required in mass microfabrication technologies, and a free-electron laser based on an energy recovery linac (ERL) is an attractive candidate. The design beam current is 9.75 mA, and the beam energy is 800 MeV. The cavity design is required to achieve a target gradient of 12.5  MV/m with a high yield and efficient suppression of radiofrequency power losses through higher-order modes (HOMs). The HOMs generated in the cavity pass through the end cells and are damped by the beam-tube dampers. The cavity was designed mainly to reduce the heat generated by the monopole modes. Further, the transverse shunt impedance of dipole modes must be smaller than the specification related to the beam breakup effect. Considering the cavity design, the end cell was optimized by selecting the appropriate frequency obtained using the tuning curve method. The shape of the HOM damper was designed using the complex permittivity data obtained from the S-parameter method with sample pieces. This cavity design was confirmed to have a sufficient margin of accelerating gradient and adequately damped HOMs for the 10-mA-class ERL operation.